CULTURE AMONG YOUNG PEOPLE IN THE CONTEXT OF REFORMS - Rakhmanov Abdurauf Muhammedovich (Journal Park Publishing, 2025)
The article focuses on the development of a culture of entrepreneurship among young people and the creation of its legal mechanisms. In consequence the concept of a culture of entrepreneurship and the factors influencing its formation has been analyzed. Furthemore, it states that whithin the national, spiritual and universal values in the formation of a culture of entrepreneurship among young people in the context of reforms it is exact to pay a proper attention to a moral points of the given issue conserning reforms being implemented in our country.
Keywords: Entrepreneurship, entrepreneurial culture, moral values, honesty, national values, self-sacrifice, legal culture, universal human values, justice, rule of law, conscience, honor, phenomenon.